Assessment of nutritional support in patients after liver and kidney transplantation - Ćurić Delač, Maja; Flegar-Meštrić, Zlata; Perkov, Sonja; Borovac Štefanović, Leda; Vidas, Željko; Kocman, Branislav; Jadrijević, Stipislav; Aladrović, Jasna; Mandelsamen Perica, Marina; Delaš, Ivančica (2019)
During the last decades organ transplantation has evolved into a proven therapy for end-stage organ failure. However, the long-term success of organ transplantation depends significantly on the patients’ ability to overcome possible postoperative complications and to recover from a severe metabolic imbalance. Therefore, in the present study we assessed the accuracy of the early post-operative nutritional intake in a vulnerable group of patients after organ transplantation and compared it with the calculated minimal nutritional requirements. A number of 61 patients were included in the study, 48 with liver, 11 with kidney, and two patients with both, liver and kidney transplants. Mini nutritional assessment (MNA) was applied and total nutritional intake was recorded for fourteen consecutive post-transplant days. Serum concentrations of proteins, urea and creatinine, as well as catalytic concentrations of liver enzymes were measured. Urea to creatinine ratio was calculated. According to body mass index (BMI) only a few patients were malnourished, but low serum protein levels indicated a significant protein catabolism. Nutritional requirements were provided mainly by glucose, with low amounts of proteins, i.e. amino acids, and fats. It took more than seven days to reach the appropriate nutritional intake. Because of the intensive catabolism, especially of proteins, nutrition of organ transplant recipients requires permanent monitoring and better nutritional support through formulas for enteral and total parenteral nutrition.
Tijekom posljednjih desetljeća transplantacija organa razvila se u metodu odabira za terapiju pacijenata s terminalnim zatajenjem organa. Međutim, dugoročni uspjeh transplantacije organa ovisi o sposobnosti pacijenata da prevladaju moguće postoperativne komplikacije i da se oporave od teških poremećaja metaboličke ravnoteže. Stoga smo u ovoj studiji željeli procijeniti kvalitetu rane postoperativne prehrane u vrlo ranjivoj skupini bolesnika nakon transplantacije organa i usporediti nutritivni unos s međunarodnim preporukama kako bi se zadovoljili minimalni nutritivni zahtjevi. U istraživanje je uključen 61 pacijent, od kojih 48 s transplantiranom jetrom, 11 s transplantiranim bubregom i dva bolesnika kojima su transplantirana oba organa. Procjena rizika od malnutricije provedena je primjenom upitnika “Mini nutritional Assesment” i tijekom prvih četrnaest dana nakon transplantacije bilježen je ukupni dnevni nutritivni unos. U serumu pacijenata izmjerene su koncentracije proteina, uree i kreatinina, katalitičke koncentracije jetrenih enzima i određen je molarni omjer ureje i kreatinina. Prema vrijednostima indeksa tjelesne mase (BMI) samo je manji broj pacijenata pothranjen, ali smanjena koncentracija proteina u serumu ukazuje na značajan katabolizam proteina. Nutritivne potrebe pacijenata nakon operacije namiruju se uglavnom glukozom i manjim količinama proteina, tj. aminokiselina, dok je unos masti zanemariv. Odgovarajući postoperativni unos nutrijenata i energije postiže se nakon više od sedam dana. Zbog intenzivnog katabolizma, posebice proteina, prehrana pacijenata nakon transplantacije organa zahtijeva trajno praćenje i bolju nutritivnu potporu kroz pripravke za enteralnu i parenteralnu prehranu.
Bibliografija: 27 jed.
Abstract ; Sažetak.
Keywords: Transplantacija organa -- Prehrana pacijenata -- Proteini -- Energetski unos -- Nutritivne potrebe -- Jetra -- Bubrezi